Abolition of mandated joint‐audit requirements: Impact on audit reporting lag in an emerging capital market. Issue 1 (28th December 2022) - Van der Zahn, J.‐L. W. Mitchell
Abstract : The study aims to examine how changes in the Kuwait audit market following abolition of mandated joint‐audit requirements impact audit reporting lag. Analysis tests whether joint‐/solo‐audit switches (following abolition mandated requirements) affected the level and change in audit reporting lag. The study also tests if the joint‐audit pair combination is a decisive factor in determining the (a) level and change in audit reporting lag and (b) audit quality following a switch to a solo‐audit. Data is collected from 132 Kuwait‐incorporated, nonfinancial firms listed continuously on the Boursa Kuwait from 2015 to 2019 that provides 660 firm‐year observations (528 firm‐years main empirical tests). Analysis indicates that the following abolition of mandated joint‐audit requirements, Kuwait listed firms swiftly switched to solo‐audits, generally leading to a significant increase in audit reporting lag. Tests indicate that audit reporting lag was significantly less for joint‐audits relative to solo‐audits. Additional results show a significant negative association between the quality of joint‐audit pair combinations and audit reporting lag. However, there is no significant association between audit reporting lag and the quality of solo‐audit type. Test results indicate mixed support for the perception that a joint‐audit pair combination significantly influences the level and change in audit reporting lag following the switch to a specific solo‐audit type.